Real-time open-source FLIM analysis - Tan, Kevin K. D.; Tsuchida, Mark A.; Chacko, Jenu V.; Gahm, Niklas A.; Eliceiri, Kevin W. (Frontiers in Bioinformatics, 2023)
Fluorescence lifetime imaging microscopy (FLIM) provides quantitative information on the chemical microenvironment of the fluorophore. Analysis of data from the widely used timecorrelated single photon counting (TCSPC) implementation of FLIM is usually a post-acquisition operation due to lengthy computation times and the lack of real-time analysis toolkits that are open source and accessible. Typically, the quality of FLIM data is uncertain until after collection, and it is frequently accounted for by extending the duration of the imaging session. However, such lengthy FLIM collection sessions can not only cause important biological events to be missed but also result in unwanted photobleaching and photodamage to the samples. FLIM data collection would therefore benefit from tools to assess during imaging when and if sufficient data has been collected to accurately identify the underlying FLIM signature of a molecule and make relevant conclusions. We present the first open-source program that enables FLIM analysis while the specimen is still being scanned by combining acquisition with real-time computational and visualization capabilities. Our open-source real-time FLIM viewer is a Napari plugin that displays phasor analysis and rapid lifetime determination (RLD) results computed from data sent on the fly from acquisition software, such as the open-source Micro-Manager based OpenScan package. By providing preliminary analysis during acquisition, our method allows early identification of FLIM signatures and assessment of data quality, speeding up the imaging process for sensitive live biological samples.